Development of E-Learning Module for Lathe Machining Techniques with a Service-Learning Approach in Vocational High Schools - Suwondo Suwondo; Refdinal Refdinal; Ambiyar Ambiyar; Aswardi Aswardi (STAI Hubbulwathan Duri, 2024)
This study addresses the limitations in current learning tools for vocational machining skills, which impede active engagement, independent study, and optimal learning outcomes. To address these challenges, an e-module for Lathe Machining Engineering was developed using a Service Learning approach to enhance learning effectiveness through valid, practical, and effective instructional resources. The development followed the ADDIE model, encompassing Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected from teachers, subject-matter experts, and students to assess the e-module's validity, practicality, and effectiveness. Descriptive statistics were used for data analysis. The e-module was found to be valid across multiple criteria: content feasibility (0.85), presentation quality (0.86), language suitability (0.82), Work-Based Learning (WBL) alignment (0.94), and incorporation of the Service Learning approach (0.83). Practicality was high, with student and teacher responses averaging 90.8%. Effectiveness, measured by a gain score of 0.60, fell in the medium category, indicating improved learning outcomes. The findings suggest that the Service Learning-based e-module is a robust learning medium for enhancing machining competencies in vocational education. Its integration of active learning principles addresses gaps in engagement and independent study, supporting its practical application in technical education settings. The Lathe Machining Engineering e-module, grounded in a Service Learning approach, is valid, practical, and effective. Future research should explore its long-term impact on student performance and adaptability across diverse technical disciplines.